ANALISIS KEBIJAKAN PENDIDIKAN ISLAM DI MALAYSIA TINJAUAN HISTORIS KEBIJAKAN PENDIDIKAN ISLAM DI MALAYSIA TINJAUAN HISTORIS - Salman - (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2020)
Education plays a key role in realising Malaysia’s aspirations to be a developed nation. Malaysia’s achievement in education enrolment is significant. This is because the policies given in the education stage are very much considered. This policy emerged after independence in 1957. The policy towards Islamic education was included in national legislation. So that schools that were originally funded by the guardians of students, after the education law was issued, the state began to disburse development costs. Among the important things of this law is equal distribution of competent teachers in their fields.